Writing mothers: Criminalising the maternal figures in contemporary Taiwanese crime fiction - Kumpai, Apiwat; Pumpaisanchai, Norrarat (Humanities, Arts and Social Sciences Studies, 2023)
Female perpetrators are fairly common in contemporary Taiwanese crime fiction, yet little is known about criminal mothers who engage in child abuse or commit deliberate killings due to maternal ambivalence. This research examines the depictions of criminal mothers in three Taiwanese crime novels between 2018 and 2021: Kun Lun’s Buneng rang laoshi faxian de baling riji (2018), Ling Jing’s Zuofu tongzi (2021), and Si Xian’s Baoqian, wo taoyan wo de haizi (2021). The purpose of this research is to understand how criminal mothers are depicted and the sociological dimensions of maternal ambivalence concerning their violent behaviours. The research reveals that societal expectations of motherhood give rise to maternal ambivalence, not just the mother-child relationship alone. These mothers are struggling with patriarchal motherhood. Domestic violence, such as child castration, psychotic infanticide, and unwanted child filicide, is driven by maternal ambivalence caused by overburdening family responsibilities, gender discrimination, and the patriarchal mandates of motherhood. However, these mothers cannot be easily categorised as “bad” mothers because they also portray a non-threatening image of loving and nurturing mothers according to the ideology of motherhood. Thus, they cannot be described as morally good or bad due to blurred moral distinctions.